Viktor Franz Freiherr von Andrian-Werburg Österreich wird meine Stimme erkennen lernen wie die Stimme Gottes in der Wüste, Tagebücher 1839-1858, Band 3: Tagebücher 1854-1858 - Adlgasser, Franz (2011)
Viktor Franz Freiherr von Andrian-Werburg (1813-1858) was and still is primarily known as the author of Österreich und dessen Zukunft, the most important programmatic brochure of the estatist opposition in the late Vormärz. But it is almost unknown, that he kept a diary for most of his adult life. These diaries are now presented in a scholarly edition. Between the first entry of 20 October 1839 and the last surviving entry of 10 March 1858 lie 19 years which transformed Andrian from a young subordinate public servant in Northern Italy, Istria and Vienna to the idol of the Vormärz opposition, from a respected member and vice-president of the National Assembly in Frankfurt and German envoy in London to the proscribed demolisher of the pre-revolutionary paradise, from the advisor of the Austrian politicians in the years past 1849 to the member of the boards of capitalist railway companies in the 1850s. Throughout this whole time, Andrian saw himself as an unrecognized genius who could have rescued society from the oppression and stagnancy of the Vormärz and from the chaos of the revolution and lead it towards a better future. During all these years, the diaries show a mixture of private and public events. Reflections on family, friends, and personal developments are blended with statements and reflections on politics and policy and Andrian's own role in public life. While focus and denseness of the entries change along with Andrian's private and political situation, at center stage is always the interest in the developments in Austria and her future constitution in close connection with his personal conditions. It is this interaction between public interest and private experience that make the Andrian diaries one of the most impressive private sources on Austrian history from the Vormärz through the revolutionary years of 1848/49 well into the last years of the Neoabsolutism. Narratives about financial problems and strategies for a solution, for example through a rich marriage, alternate with analyses of internal and foreign politics and plans on the re-creation of Austria. Phases of active political involvement change with periods of voluntary and enforced retreat. Therefore, there are entries on discussions with leading politicians and court dignitaries and on audiences with Emperor Francis Joseph as well as accounts of journeys from Helgoland to Rome, from the French Atlantic coast to the South of Egypt. But the central aspect is always the interplay between private experience and public influence. Viktor Andrian felt to be a born leader, not a subordinate, and believed that he could wait for the moment when he was called to lead. Therefore he remained, with the exception of the revolutionary period of 1848/49 when he got actively involved in politics, an observer, adviser and critic at the fringes, waiting for the moment when the reins of power would fall to him. Although he realized in his later years that this was an illusion, Andrian was complacent with his personal development: "Thank God, I never had to blame myself for wicked, vicious things." This edition in three volumes contains the annotated diary entries, an introduction on Viktor Andrian's life and works, an account of the history of the diaries, and, for the first time, a complete listing of Andrian's publications. Numerous excerpts from Andrian's preserved correspondence in the commentary complement and broaden the diaries. An annotated index refers to more than 2.800 persons mentioned in the entries.